2021
DOI: 10.1002/asl.1029
|View full text |Cite
|
Sign up to set email alerts
|

Comparing diagnosed observation uncertainties with independent estimates: A case study using aircraft‐based observations and a convection‐permitting data assimilation system

Abstract: Aircraft can report in situ observations of the ambient temperature by using aircraft meteorological data relay (AMDAR) or these can be derived using modeselect enhanced tracking data (Mode-S EHS). These observations may be assimilated into numerical weather prediction models to improve the initial conditions for forecasts. The assimilation process weights the observation according to the expected uncertainty in its measurement and representation. The goal of this paper is to compare observation uncertainties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…(2015) and Mirza et al . (2021) have found good qualitative and quantitative agreement with diagnosed estimates, respectively. None of these studies has considered the effects of statistical sampling error on the diagnosed estimates, although noisy estimates have been observed (Waller et al ., 2019).…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…(2015) and Mirza et al . (2021) have found good qualitative and quantitative agreement with diagnosed estimates, respectively. None of these studies has considered the effects of statistical sampling error on the diagnosed estimates, although noisy estimates have been observed (Waller et al ., 2019).…”
Section: Introductionmentioning
confidence: 59%
“…The assumed error statistics refer to those used in the assimilation system, which are approximations of the true error statistics. Nevertheless, empirical metrological studies by Chun et al (2015) and Mirza et al (2021) have found good qualitative and quantitative agreement with diagnosed estimates, respectively. None of these studies has considered the effects of statistical sampling error on the diagnosed estimates, although noisy estimates have been observed (Waller et al, 2019).…”
Section: Introductionmentioning
confidence: 91%
“…Li (2021) showed that assimilating Mode‐S winds has a positive benefit on the forecast skill in wind profiles in the first 6 h of the forecast, and for hourly precipitation accumulations up to 9 h into the forecast. The assimilation of Mode‐S EHS temperature data is more challenging as the temperature observations have been shown to be of lower quality, particularly in the boundary layer (Mirza et al, 2016; Mirza et al, 2019; Mirza et al, 2021). However, these data can be used after some processing (de Haan, 2013; de Haan & Stoffelen, 2012).…”
Section: Progressmentioning
confidence: 99%
“…It might be desirable to corroborate error observation estimates from either DBCP or 3CH in alternative ways by, for example, making use of independent observations (e.g., Ménard and Deshaies-Jacques, 2018;Mirza et al, 2021. The generality of two of the corners of 3CH offers yet another possibility for a methodology to obtain alternative estimates. This is the gist of the work of Anthes et al (2022).…”
Section: General Remarksmentioning
confidence: 99%